A case study exploring the 'real world' process of 'naturalizing' school playgrounds. Issue 3 (3rd April 2021) - Harper, N. J.; Lim, C.; Alqallaf, H.; Naylor, P. J.
ABSTRACT: Background:  The aim of this study was to examine the lived experiences of teachers and administrators at two schools (one elementary Kindergarten-Grade 5 and one middle school, grades 6–8) following the 'naturalizing' of a portion of their schoolyard. Methods : A qualitative case study design was used. Focus groups and interviews allowed participants to express their rationale, identify implementation facilitators and barriers and critical processes/steps for realizing their naturalization goals. Researcher questions explored (1) factors which led to naturalizing the schoolyard, (2) key planning and process steps (3) challenges and successes experienced, and, (4) lessons learned. Findings : Six themes were identified as rationale for naturalizing including: re-integration of outdoor play into children's daily lives, pro-active mental health, opportunity for inclusion, nature as a positive space for learning, it fit with our values and principles, we had a need. Implementation was facilitated by having champions and support from multiple levels, adopting a phased approach, resources and having the buy-in to persevere over time. Significant challenges and 'how to' steps were also identified. Conclusions : Naturalizing schoolyards does not happen without a supportive context, significant time and effort. Implementation steps and issues were those commonly found in other school-based health promotion efforts.